Cerebral Fat Embolism in a Patient With Hemoglobin SC Disease Associated With Vaso-Occlusive Crisis and COVID-19 - Zachary Buxo; Astha Saini; Cullen Hudson; Diane L. Levine (Annals of Internal Medicine: Clinical Cases)
Sickle cell disease is characterized by episodic vaso-occlusive events triggered by a combination of inflammation, increased adhesion to vascular endothelial cells, and activation of hemostasis. This vascular obstruction results in acute vaso-occlusive pain, stroke, and acute chest syndrome, which are more commonly observed when patients are admitted for acute vaso-occlusive crisis. Although fat embolism syndrome is most associated with orthopedic trauma, individuals with sickle cell hemoglobinopathy are at increased risk for nontrauma-related fat embolism syndrome. Here we describe a young woman with a history of hemoglobin SC disease who presented with fat embolism syndrome following a vaso-occlusive crisis precipitated by COVID-19 infection.